Writing Open Architecture as a book on Human Rights (and against Nation-States) - Esra Akcan (Footprint)
Drawing on the author’s book Open Architecture, this essay studies the relation between migration and architecture as a matter of human rights, and thereby exposes the historical roots of contemporary racisms, while giving due acknowledgment to the Black and Brown migrants in the making of even the most established European architectural projects. This analysis not only exposes the weaknesses of a world order predicated on the limited and constructed idea of the nation-state, but also outlines architecture’s ways to build resistance through the concept of openness. Defining open architecture as a new ethic of welcoming toward the immigrant, the essay alludes to the formal, programmatic and procedural aspects of latent open architecture, such as flexibility and adaptability of form, collectivity and collaboration, participatory processes, and multiplicity of meaning.